THE ROLE OF TWITTER IN GEN Z ENGLISH DEVELOPMENT - Ira Irzawati; Agnes Felisya Unamo; Kayla Natasha (Universitas PGRI Palembang, 2024)
Technology development has led to the rise of social media, which affects all facets of a person's life, including Gen Z. The purpose of this study is to show Gen Z's overall opinions about Twitter's contribution to their English language development. In this poll, 84 Gen Z participants, ranging in age from 15 to 27, from diverse backgrounds and residences across Indonesia, took part. The participants divulged their answers to the survey questions concerning Twitter's contribution to the evolution of Gen Z English. Simple percentage analysis was used to examine the respondents' questionnaire responses, and the results were explained in relation to relevant theories and earlier research. This study revealed that Twitter plays a significant role in fostering the development of Gen Z English. Twitter not only helps Generation Z become more fluent in English, but it also gives them a platform to voice their opinions, share information, promote themselves, and engage in communication. This study offers useful data and fresh perspectives that may help us comprehend the part social media plays in Gen Z's English development.